“Quotations” in headlines: their analysis in two German regional newspapers as a contribution to the topic of language usage in the media / „Zitate“ in Schlagzeilen: eine medienlinguistische Untersuchung am Beispiel zweier deutscher Regionalzeitungen - Geyer, Klaus (Kalbotyra, 2008)
Based on a corpus of articles from two regional subscription newspapers representing the most widespread type of daily papers in Germany, this contribution analyses quotations in headlines of press articles and their relation to the corresponding sequences in the text body, thus focussing on the quotations’ intratextual reference quality. It turns out, that a considerable part of these “quotations” shows modifications of the formulations given in the text body. How the modifications are actually formed is modelled by a five-stage scale, and which functions they fulfil is illustrated by selected examples.